Uprość wyrażenie
(3y − x)(2x + y)
a następnie oblicz jego wartość liczbową dla x = 1/2, y = -1 *

Daje naj pls szybko


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

(3y-x)*(2x+y) = 6xy + 3[tex]y^{2}[/tex] - 2[tex]x^{2}[/tex] - xy = 5xy + 3[tex]y^{2}[/tex] - 2[tex]x^{2}[/tex]

x = [tex]\frac{1}{2}[/tex] , y = -1

5* [tex]\frac{1}{2}[/tex] *(-1) + 3* (-1)² - 2* ( [tex]\frac{1}{2}[/tex] )² = -[tex]\frac{5}{2}[/tex] + 3 -  [tex]\frac{1}{2}[/tex] = - 2[tex]\frac{1}{2}[/tex] + 3 -  [tex]\frac{1}{2}[/tex]  =  [tex]\frac{1}{2}[/tex]  -  [tex]\frac{1}{2}[/tex] = 0